Evoked Culture and Evoked Nature: The Promise of Gene-Culture Co-Evolution Theory for Sociology - Walsh, Anthony; Yun, Ilhong (Frontiers in Sociology, 2016)
The traditional sociological view of culture has been almost exclusively that of transmitted culture decoupled from biology. The concept of evoked culture brings biology “back in” since it identifies ecological challenges that evoked certain practices based on evolutionary imperatives. The practices are then passed on to subsequent generations as normative, and individuals best suited to these normative practices will enjoy greater fitness benefits than those less suited. In other words, practices will be transmitted genetically as well as culturally. This paper provides several examples of how evoked and transmitted culture are tightly bound (nature evoked by culture, and culture evoked by nature) as well as identifying two specific genetic polymorphisms associated with adaptive approach-avoidance behaviors and found in highly variable frequencies in different cultures around the world. We argue that an appreciation of evoked culture complements transmitted culture and deepens and broadens our understanding of cultural life and practices.